2014
DOI: 10.1590/1413-81232014198.19882013
|View full text |Cite
|
Sign up to set email alerts
|

Inatividade física em idosos não institucionalizados: estudo de base populacional

Abstract: Inatividade física em idosos não institucionalizados: estudo de base populacionalPhysical inactivity among non-institutionalized elderly individuals: a population-based study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
3
11
0
16
Order By: Relevance
“…2,17 The higher prevalence of physical inactivity among elderly men contradicted the findings of studies by Alves et al 1 and Queiroz et al, 2 which found no difference in the prevalence of physical inactivity between the genders. This result can be attributed to the presence of a culturally constructed model of masculinity, in which men are considered to be strong and tough, According to this study, the social representation of the health and disease process for men is connected with its curative aspect, while for women the same process is more linked with its preventive aspect.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…2,17 The higher prevalence of physical inactivity among elderly men contradicted the findings of studies by Alves et al 1 and Queiroz et al, 2 which found no difference in the prevalence of physical inactivity between the genders. This result can be attributed to the presence of a culturally constructed model of masculinity, in which men are considered to be strong and tough, According to this study, the social representation of the health and disease process for men is connected with its curative aspect, while for women the same process is more linked with its preventive aspect.…”
Section: Discussionmentioning
confidence: 86%
“…[1][2][3] In the opinion of the World Health Organization, this tendency represents a major public health problem and a major modifiable risk factor for the development of chronic noncommunicable diseases (CNCD). 4,5 Physical inactivity is considered the fourth greatest risk factor for mortality, contributing to the death of approximately 3.2 million people every year.…”
Section: Introductionmentioning
confidence: 99%
“…O mundo está em processo de envelhecimento 2 , e no Brasil, este vem ocorrendo de forma acelerada nas últimas décadas 3,4 . Estima-se para o ano de 2050, no Brasil, bem como em todo o mundo, a existência de mais idosos que crianças abaixo de 15 anos 2 , e segundo a Organização Mundial da Saúde 5 já em 2025, o Brasil será o sexto país do mundo em número de idosos.…”
Section: Introductionunclassified
“…É um processo fisiológico que não necessariamente ocorre paralelamente à idade cronológica e que apresenta considerável variação individual 6 . Doenças crônicas e degenerativas aparecem com o decorrer do envelhecimento, contribuindo para a diminuição das habilidades necessárias para a vida diária e um importante marcador de um envelhecimento bem sucedido e de uma ótima qualidade de vida nos idosos é a capacidade funcional 2,4,7 . Para uma efetiva prevenção, ou mesmo para a redução das perdas funcionais que estão associadas ao envelhecimento, sugere-se a inclusão num programa regular de exercícios físicos 4,8,9 .…”
Section: Introductionunclassified
See 1 more Smart Citation